Enhancing Learners' Object-Oriented Programming Skills through the Integration of Block Model and UML Class Diagram - Hu, Chih-Chien; Chen, Ming-Hsien (IEEE International Conference on Consumer Electronics-China (Online), 2025)
Java Object-Oriented Programming (OOP) is vital in information technology, but students often struggle with abstract concepts and complex logic. This study applies the Block Model (BM) to segment instructional content, reducing learning pressure and improving understanding and application skills. Integrating UML class diagrams with BM creates a structured teaching framework for Java OOP. Results show significant post-test improvement, validating this approach. However, algorithmic thinking remains challenging, requiring structured problem-solving, debugging exercises, and adaptive learning. Generative AI-driven coding support could further enhance engagement and long-term retention.